The impacts of economic policies and the role of capitalists in economic development during the Reign of King Rama VII - Tamajai, Anusorn; Petchlertanan, Thamrongsak (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2024)
This qualitative research examined the role of economic policy and capitalism development during political and economic transitions of King Prajadhipok (Rama VII) of Thailand. Socioeconomic and political backgrounds, development of capitalism by different groups from 1925 to 1934, and relevant economic policies were studied. Capital accumulation and growth based on a patronage system. Economic Policies have fostered the semi-feudal capitalist economic system to be able to continuously operate during the reign of King Rama VII. Several policies have significantly coherence and affected to various policies. Almost all capitalist groups before the Siamese revolution of 1932 accumulated capital through relationships with state power during the era of absolute monarchy. Rent seeking and deadweight loss impacted social welfare. Stakeholders with significant roles in investment and trade developed from formerly patronized state capitalist and Royal Treasury groups, Thai Chinese and Western businesspeople. Europeans and Americans were increasingly present after the Bowring Treaty. These capitalist groups invested in new technology and exploited natural resources. Most from 1925 to 1934 were traders lacking power to change economic fundamentals in Thailand. Industrial development slowed due to absence of strong internal industrial capital